Hybrid ultramicroporous materials (HUMs) with enhanced stability and trace carbon capture performance. Issue 44 (3rd May 2017) - Kumar, Amrit; Hua, Carol; Madden, David G.; O'Nolan, Daniel; Chen, Kai-Jie; Keane, Lee-Ann J.; Perry, John J.; Zaworotko, Michael J.
Abstract : Fine-tuning of HUMs through pillar substitution can significantly enhance trace CO2 sorption performance and stability. Abstract : Fine-tuning of HUMs through pillar substitution can significantly enhance trace CO2 sorption performance and stability. The resulting materials, exemplified by the new material TIFSIX-3-Ni, [Ni(pyrazine)2 (TiF6 )] n, are shown through temperature programmed desorption experiments to remove trace quantities of CO2 from moist gas mixtures.